A relação entre estágio curricular supervisionado obrigatório e trabalho de conclusão de curso no contexto da transferência de tecnologia nos cursos de engenharia: um estudo na UTFPR - Câmpus Ponta Grossa - Ramos, Wilson (2016)
This paper has the general objective of checking if the Mandatory Supervised Internships are potential generators of themes for Final Term Papers in engineering majors, with focus on technology transfer. The present study employed an applied research, exploratory and descriptive. The research data was collected from students enrolled in the class Final Term Papers II, in the Engineering Majors of UTFPR – Ponta Grossa Campus. For the data gathering, a semi-structured questionnaire with open questions was used. The paper is divided in stages and scenarios in order to facilitate the understanding of the results. Stage 1 describes how is the internship and final term paper situation according to the responses of the students participating in the research. This stage generated the scenario 1, representing the students who are performing the flow that best furthers the process for technology transfer in the researched majors, and the scenario 2, where the possibility of the internship influencing the choice of theme for the Final Term Paper, which is already underway, is almost null. Stage 2, Elaborated from the result of scenario 1, seeks to understand the reason why the internship did not generate the Final Term Paper theme. Stage 3, also elaborated from the result of scenario 1, approached the students, through a structured interview, with the purpose of getting to know the reason that led them to develop the Final Term Paper through the internship. This research finds that the relation between the internship and the Final Term Paper is minimal, presented by the result of scenario 1. One of the identified drawbacks is the possibility of the student being able to write the Final Term Paper before the internship, supported by the curriculum guidelines in the engineering majors of UTFPR, described in the theoretical framework and confirmed by the responses of ten students in the result of stage 2. Developing a paper focused on the company assigning the internship may also be considered a facilitator for the technology transfer process. The respondent R3 believes that it may be a differential for the intern as well as for the company. The student developed a project in which he had to study coding and understand how transmission equipment works. Adding to this Idea, the respondent R5 comments that, when developing a project for the company, the intern must show the obtained results and prove that these results can generate profits for the organization. As a suggestion, this paper proposes the creation of an archive where it would be possible to store all the internship reports and the Final Term Papers of the engineering majors, intending to provide researches for future students. As a suggestion for future papers, to participate in public defenses of internship reports as well as in Final Term Papers presentations, delimiting by major.